Tanggung Jawab Notaris dalam Menjamin Kepastian Hukum dan Itikad Baik (Studi Putusan Mahkamah Agung Nomor 1442 K/Pdt/2024) - Fertika Yuliandari; Rosnidar Sembiring; Maria (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The position of notaries as public officials who draw up authentic deeds is an important pillar in realising legal certainty and ensuring the principle of good faith between parties in every civil law transaction. It is not uncommon for notaries to be suspected of involvement or at least negligence in supervising the fulfilment of these two principles, so that deeds that were originally intended as a means of legal protection instead become a source of dispute and harm to one of the parties. One notable case is Supreme Court Decision Number 1442 K/Pdt/2024 concerning the responsibility of notaries in the preparation of authentic deeds. The method used was normative legal research. The results of the study show that the notary's responsibility is not only formal and procedural; in principle, the notary can be held administratively, civilly, or criminally liable in accordance with the level of fault and their role in the unlawful act that occurred.